2018
DOI: 10.1186/s12906-018-2270-1
|View full text |Cite
|
Sign up to set email alerts
|

Water extract of Clinacanthus nutans leaves exhibits in vitro, ex vivo and in vivo anti-angiogenic activities in endothelial cell via suppression of cell proliferation

Abstract: BackgroundClinacanthus nutans (Burm. f.) Lindau. has traditionally been using in South East Asia countries to manage cancer. However, scientific evidence is generally lacking to support this traditional claim. This study aims to investigate the in vitro, ex-vivo and in vivo effects of C. nutans extracts on angiogenesis.MethodsC. nutans leaves was extracted with 50–100% ethanol or deionised water at 1% (w/v). Human umbilical veins endothelial cell (HUVEC) proliferation was examined using MTT assay. The in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…According to the National Cancer Institute (NCI), a crude extract that exhibits an IC 50 value <20 μg/ mL can be considered as an active anticancer agent. This finding is supported by a previous study (Ng et al, 2018), that reported 50, 70 and 100% ethanol extract of C. nutans did not affect endothelial viability regardless of its concentrations up to 100 μg/ml even with prolonged treatment time from 24 to 72 hours. The antiproliferative activity of ethanolic extract (D) is the highest against MCF7 (breast cancer) and the lowest against CRL2522 (normal fibroblast) cell line.…”
Section: E-issn 2477-0612supporting
confidence: 89%
“…According to the National Cancer Institute (NCI), a crude extract that exhibits an IC 50 value <20 μg/ mL can be considered as an active anticancer agent. This finding is supported by a previous study (Ng et al, 2018), that reported 50, 70 and 100% ethanol extract of C. nutans did not affect endothelial viability regardless of its concentrations up to 100 μg/ml even with prolonged treatment time from 24 to 72 hours. The antiproliferative activity of ethanolic extract (D) is the highest against MCF7 (breast cancer) and the lowest against CRL2522 (normal fibroblast) cell line.…”
Section: E-issn 2477-0612supporting
confidence: 89%
“…The results of their study show that there is a significant correlation between LD50 values generated using the CAM versus mice and therefore the test could be used in preliminary studies to reduce testing time and the number of animals. Ng et al [27] have used in their study Suramin as a positive control to inhibit vessel sprouting in a CAM model. They have used this standard to demonstrate that Clinacanthus nutans water extract prevents new blood vessel formation in the CAM model.…”
Section: Discussionmentioning
confidence: 99%
“…The main functions of CAM are: respiratory organ for the embryo, storage membrane of excretions and also membranes for mobilization of calcium from the shell to start bone mineralization [17]. The CAM assay was performed according to Kue C.S., et al, 2015 and Theng Ng C., et al 2018 [26,27] with some modifications. For this purpose, hen eggs were incubated at 37 • C under 60-70% relative humidity.…”
Section: In Vivo Evaluation Of Angiogenic Activity Using a Cam Modelmentioning
confidence: 99%
“…For the past few decades, the research for C. nutans has been progressively done in a rapid trend. Broad-spectrum of pharmacological activities, which includes antioxidant [ 4 ], antiviral (herpes simplex virus (HSV), varicella-zoster virus, papillomavirus, and dengue virus) [ 5 ], anti-inflammatory [ 6 ], antibacterial [ 7 , 8 , 9 ], analgesic [ 10 , 11 , 12 ], antivenom [ 13 , 14 , 15 ], immunomodulating [ 16 , 17 ], neuroprotective [ 18 , 19 , 20 ], antidiabetic [ 21 , 22 , 23 ], α-glucosidase inhibitory [ 24 ], lipid-elevated inhibition [ 25 ], plasmid DNA protective [ 26 ], anti-angiogenic [ 27 ], anticancer [ 28 ], anti-proliferative [ 28 ], and antitumor as the latest biological action identified [ 29 ], has been very well reported in previous studies. Owing to significant economic benefits towards human health, the demand for this herb has been increased in recent years.…”
Section: Introductionmentioning
confidence: 99%